Comparison of Anterior-Cruciate Ligament Tear in Adults and Adolescent Patients - Agha Momin, Muhammad Shahbaz Raza, Kamran Saeed, Sikander Ali Bhurgri, Naeem Mehmood Mughal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the anterior-cruciate ligament tear in adults and adolescent patients. Study Design: Retrospective study Place and Duration of Study: Department of Orthopaedics, Pak Red Crescent Medical & Dental College, Dina Nath from 1st January 2020 to 31st December 2021. Methodology: One hundred patients were enrolled and they divided into two groups, each having 50 patients. Group I had patients within the age group 12-20 years while in Group II had patients within the age of >20 years. Demographic details of each patient and their clinical history was recorded. A radiological information system applied for imaging interpretation with neutral-rotation of knee up to 10-15ᵒ flexion. Results: The mean age of group I patients was 17.5±1.5 years and group II patients was 31.2±2.1 years with more males between both groups than females. There were 19 right and 31 left knees in group I and 21 right and 29 left knees in group II respectively. The tibial-internal rotation had a comparatively significant degree increase in group II in comparison with group I. Conclusion: In adults the tibial-internal rotation had a comparatively significant degree increase than adolescents.